ANALISIS PENERAPAN PEMBELAJARAN NUMERASI BERBASIS MASALAH KEHIDUPAN SEHARI-HARI PADA SISWA KELAS III SDN 15 PALEMBANG - Putri Widya Wati; Oktaviani; Muhamad Zulkarnain; Ana Carolina; Mareta Silaturi; Ana Swita; Mega Prasrihamni; Dian Nuzulia Armariena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to provide an in-depth analysis of the implementation of numeracy learning based on everyday life problems for third-grade students at SDN 15 Palembang. The study used descriptive qualitative methods. Data were generated through observation, interviews, and documentation. The results indicate that problem-based learning can help students understand mathematical concepts more clearly. Students' problem-solving and critical thinking skills also improve. Students are more engaged and able to connect the lesson to their daily lives. However, the implementation of the learning still faces several obstacles, such as limited learning media, differences in student ability levels, and time constraints. Overall, it is proven that contextual problem-based numeracy learning successfully improves elementary school students' numeracy skills